Prognostic effect of the pretreatment prognostic nutritional index in cervical, ovarian, and endometrial cancer: a meta-analysis - Chun Li; Yalei Yin; Zhen Yang; Qing Zhang; Wei Wang; Junqiang Liu (BMC, 2024)
Abstract Background The prognostic value of the pretreatment prognostic nutritional index (PNI) for gynaecological malignancies remain unclear. This meta-analysis aimed to explore the predictive significance of the PNI for gynaecological tumours. Methods The PubMed, Embase, Web of Science, and Cochrane Library databases were searched up to January 30, 2024, to identify relevant studies. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated to assess the associations of the PNI with overall survival (OS), progression-free survival (PFS), and disease-free survival (DFS) in patients with gynaecological tumours. We examined the correlation of the PNI with clinicopathological parameters of patients with gynaecological carcinoma by utilizing pooled odds ratios (ORs) and 95% CIs. Results A total of 28 articles involving 9,428 patients were included in the meta-analysis. The results revealed that a low PNI significantly predicted worse OS (HR = 1.60, 95% CI: 1.39-1.84, P < 0.001), PFS (HR = 1.63, 95% CI: 1.20-2.23, P = 0.002), and DFS (HR = 1.73, 95% CI: 1.19-2.52, P = 0.004). In addition, the subgroup analysis confirmed that the PNI had a prognostic effect on OS for all cancer types, but a significant association with PFS was not observed in patients with cervical cancer. A low PNI was significantly associated with FIGO stages III‒IV (OR = 2.30, 95% CI: 1.89‒2.80, P < 0.001) and LN metastasis (OR = 2.76, 95% CI: 2. 05‒3.73, P < 0.001). Conclusion The PNI may be noninvasive and promising biomarker for predicting the prognosis of patients with gynaecological tumours.